Learning from Asia's success beyond simplistic 'lesson-making' - Mike Hobday (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Many international organizations, governments and academics concerned with economic development look to Asia's success, recommending that other poor countries follow similar models and paths of development. This study argues that such Asian 'lesson-making' is a grave mistake in policy-thinking - and in the historical understanding of the nature and process of development. In identifying what we can and cannot learn from the Asian experience, this study examines the various paths of successful growth in East and South East Asia and asks: what can other developing countries learn from Asia's success, if anything? The study also examines the arguments of some of the great development thinkers of the past to ascertain what can be learned. Because technological and market circumstances facing today's developing nations have changed it is a mistake to base any strategy on the achievements of past industrializers. There can be no standard list of development prerequisites or 'best practices'. Unfortunately, the basic error of recommending 'follow the leader' catch-up policies has a long tradition in development thinking. However, several distinguished observers of past development (e.g. Gerschenkron, Kuznets, and Abramovitz) maintained that development processes and strategies must be based on the stage of development, distinctive resources, and institutions, and external conditions facing individual nations, not on the paths or models of previous industrializers. Nevertheless, the developing nations of today cannot ignore the rise of Asia and the study identifies useful insights from the Asian experience. Developing countries should (like Asia did) seek to complement not copy the growth paths of more successful economies, including Asian ones. Development ultimately requires, as it did across Asia, significant innovation and creativity in business organization, technology, wider institutional structures, and government policies.
Keywords: L52; O14; 330; Asia; innovation; lessons; economic development